Ultrasound Pretreatment Prior to Hot Air Drying and Intermittent Microwave Drying of Apple Slices: Effect of Acoustic Density and Microwave Power - Fadime Begüm Tepe; Tolga Kağan Tepe (Turkish Journal of Agriculture: Food Science and Technology)
This study investigated the impact of various drying techniques and ultrasound pretreatments on the drying kinetics, rehydration properties, energy efficiency, and quality parameters of apple slices. Apples were dried using hot-air drying at 55 °C and 65 °C, and intermittent microwave drying at 240 W and 400 W. US pretreatment was applied at acoustic densities of 60 and 80 W L⁻¹ prior to hot-air drying to assess its effect on mass transfer and quality. The drying behavior was modeled using both thin-layer mathematical models and artificial neural networks. Results revealed that US pretreatment significantly enhanced the drying rate and reduced drying time and energy consumption, particularly at higher acoustic density and temperature, while intermittent microwave drying achieved the shortest drying durations and lowest energy consumption. Among the models, the Midilli and Kucuk model best described the thin-layer drying data, although ANN models provided superior predictive performance across most conditions. Rehydration ratio was positively influenced by US pretreatment at lower temperatures but was adversely affected at higher temperatures and higher microwave power levels due to structural damage. Total phenolic content and antioxidant activity were preserved or enhanced by microwave drying, whereas US pretreatment showed no clear benefit and, in some cases, led to degradation, likely due to prolonged sonication and water immersion. Color values showed minimal undesirable changes with US pretreatment, and higher L* values (lightness) were retained in most cases. a* and b* values increased after drying processes. Principal component analysis (PCA) effectively differentiated treatment groups based on all measured parameters. US pretreated and unpretreated samples are positioned in the same place, while intermittent microwave dried and fresh samples are in a different plane. In conclusion, US pretreatment and microwave drying are promising technologies for improving drying efficiency and maintaining quality in dried apple products.